2018
DOI: 10.3390/met8121038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cryogenic Treatment on Wear Resistance and Microstructure of AISI A8 Tool Steel

Abstract: The effects of deep cryogenic treatment (DCT) on the wear behavior of different tool steels have been widely reported in the scientific literature with uneven results. Some tool steels show a significant improvement in their wear resistance when they have been cryogenically treated while others exhibit no relevant amelioration or even a reduction in their wear resistance. In this study, the influence of DCT was investigated for a grade that has been barely studied in the scientific literature, the AISI A8 air-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…Between the cryogenic temperature and holding time, the cryogenic temperature is the most influencing parameter, followed by holding time as the second influencing parameter, which agrees with the findings of Darwin et al [40]. Many researchers have found that lowering cryogenic temperature could obtain more improvement in wear resistance of steels, and the optimum value of cryogenic temperature was −196°C [9,25,41,42]. Similarly but slightly different in this work, cryogenic treatment at −160°C obtained more improvement of wear resistance than −120°C, and wear resistance at −196°C improved almost the same as −160°C, only higher by 0.29%, which may be due to the introduction of multiple cycles of cryogenic treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Between the cryogenic temperature and holding time, the cryogenic temperature is the most influencing parameter, followed by holding time as the second influencing parameter, which agrees with the findings of Darwin et al [40]. Many researchers have found that lowering cryogenic temperature could obtain more improvement in wear resistance of steels, and the optimum value of cryogenic temperature was −196°C [9,25,41,42]. Similarly but slightly different in this work, cryogenic treatment at −160°C obtained more improvement of wear resistance than −120°C, and wear resistance at −196°C improved almost the same as −160°C, only higher by 0.29%, which may be due to the introduction of multiple cycles of cryogenic treatment.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, it is essentially difficult for the carbon atoms to move diffusely during the cold treatment process. As a result, a large number of dispersed ultrafine carbides precipitate on martensite [8,22].…”
Section: Effect Of Cryogenic Treatment On Microstructurementioning
confidence: 99%
“…The main objective of the cooling methods incorporated in the study is to minimize CT [14], and to indirectly improve the tool-life by avoiding abrasion, diffusion and adhesion on the tool would be developed directly from the growth of excess CT during machining process [23][24][25]. The comparison between the three machining methods at three levels of SS were represented in figure 4.…”
Section: Cutting Temperature -Ct (ºC)mentioning
confidence: 99%